An evaluation of go2 homestay website: the website effectiveness and intention to visit / Surya Ayu Sabaruddin and Nor Hayati Ahmad Harnaini @ Abdullah - Sabaruddin, Surya Ayu; Ahmad Harnaini @ Abdullah, Nor Hayati (Faculty of Hotel & Tourism Management, 2013)
This study explores the three web-specific dimensions, firstly, information/web content; secondly, communication/content quality and finally the technical merit/web design. It investigates the issues that make a website effective and explores the importance dimensions with respect to homestay tourism websites. It briefly argued that these dimensions are unique to the website effectiveness and as such, has an implication on the web users decision to visit the attractions. This research functions is an initial step of an exploratory study to determine necessary dimension of the website effectiveness to define the concept. It then evaluates the advances research fronts in areas of effective marketing tools to attract future web browsers to actually visit the promoted attractions. A variety of standard methodologies were employed: a content review of the go2uhomestay website and a questionnaire survey of homestay tourism website users. All participants were users of website services to the trust. Demographic information was recorded for each participant. The findings from this study should be of value to the Government and tourism related bodies in terms of expanding their customer base and eventually promoting the national outstanding tourism attractions of the country. Finally, it presents recommendations for improvement of homestay tourism website effectiveness.